Support, social networks and the family in Portugal: two decades of research - Aboim, S.; Vasconcelos, Pedro; Wall, K. (International Review of Sociology, 2013)
This article presents two major surveys, carried out in Portugal, on the inclusion of families and individuals in social networks of support and affinity. The first, dating from 1999, sought comprehensively to reconstruct families' social networks by mapping effective support relations. The second survey, fielded in 2009–10, followed a family configuration perspective which sought to reconstruct individuals' networks of close relationships, and the issue of informal support only arose as providing further insight into the characteristics of personal networks. Both surveys will be analysed from a comparative perspective which, while stressing their different but connected conceptual orientations, compares each one's methodological strategies and operationalization procedures. Finally, the main results of each survey are outlined, leading to a brief discussion of the ways in which the two surveys complement each other.